Client De-Selection by a Professional Service - Jones, Victoria Collette (2006)
This research attempts to investigate the dynamics involved, concerning the ending of the professional relationship between a dentist and their patient where this is specifically initiated by the dentist. In doing so it aims to enhance the literature on business/consumer relationship dissolution that has only recently begun to be explored.